The value of polymorphism + 3725G / C TLR4 gene as a marker of liver fibrosis progression in patients with chronic hepatitis C - Bevz, T. I.; Kyrychenko, D. F.; Martynyuk, G. A. (Journal of Education, Health and Sport, 2019)
As a rule, chronic hepatitis C is manifested by the development of successive stages of liver fibrosis with the formation of eventually cirrhosis and liver cancer. However, in some patients the fibrosis progresses slowly, while in others there is a rapid formation of cirrhosis, which causes high mortality among such patients. According to published data, despite a fairly large number of studies regarding liver cirrhosis in chronic hepatitis C, factors contributing to liver fibrogenesis have not been definitively determined. The available data are quite contradictory. In this article, we review studies have assessed the TLR4 + 3725G/C gene polymorphism as a factor that may influence the rate of fibrotic progression. The research will build new approach for avoiding fast fibrogenesis.